Essentials of commercialisation of public enterprises : a report of the proceedings of the one day National Workshop on the Commercialisation Programme organised by the TCPC, 14th April 1992 - Zayyad, H.R. (Lagos, Nigeria : Technical Committee on Privatisation and Commercialisation, 1992)
This is a comprehensive literature on the subject of commercialization to guide policy makers, public enterprise and managers in heir search for economic efficiency without divestment
osc 21/01/2019
Ref.
Keywords: Privatisation; Public enterprises; Commercialisation; Economic policy